Chronic Low-Grade Inflammation in Elderly Persons Is Associated with Altered Tryptophan and Tyrosine Metabolism: Role in Neuropsychiatric Symptoms - Capuron, Lucile; Schroecksnadel, Sebastian; Féart, Catherine; Aubert, Agnès; Higueret, Denise; Barberger-Gateau, Pascale; Layé, Sophie; Fuchs, Dietmar (Biological psychiatry (1969), 2011)
Neuropsychiatric symptoms are common complaints of elderly persons. Recent data suggest that chronic low-grade inflammation, a fundamental characteristic of aging, plays a role. Effects might rely on the influence of inflammation on the activity of two enzymatic pathways, the indoleamine-2,3-dioxygenase (IDO) and the guanosine-triphosphate-cyclohydrolase-1 (GTP-CH1) pathways, which are involved in the biosynthesis of monoamines. The present study assessed this possibility in 284 healthy elderly subjects drawn from the Three-City cohort. Assays included the measurement of serum interleukin-6 and C-reactive-protein, as inflammatory markers; tryptophan, kynurenine, and their ratio as index of IDO activity; and neopterin, phenylalanine, tyrosine, and nitrite, as markers of GTP-CH1 activity. In addition, structured assessments of depressive symptomatology, fatigue, and general behavioral/neurovegetative symptoms were performed. As expected, age correlated significantly with concentrations of immune markers and neuropsychiatric symptoms. Increased inflammation was related to reduced tryptophan concentrations and increased kynurenine levels, suggestive of IDO-induced increased tryptophan catabolism. In addition, inflammation was associated with increases in neopterin and nitrite levels and in phenylalanine concentrations at the expense of tyrosine. Interestingly, increased tryptophan catabolism was associated with the depressive symptoms of lassitude, reduced motivation, anorexia, and pessimism. In contrast, variations in markers of GTP-CH1 activity correlated more with neurovegetative symptoms, including sleep disturbance, digestive symptoms, fatigue, sickness, and motor symptoms. These findings show that chronic low-grade inflammation in aging is associated with alterations in enzymatic pathways involved in monoamine metabolism and suggest that these alterations might participate in the pathophysiology of neuropsychiatric symptoms in elderly persons.